Dissociation dynamics of the water dication following one-photon double ionization. II. Experiment - Reedy, D.; Williams, J. B.; Gaire, B.; Gatton, A.; Weller, M.; Menssen, A.; Bauer, T.; Henrichs, K.; Burzynski, Ph.; Berry, B.; Streeter, Z. L.; Sartor, J.; et al. (My University, 2018)
We demonstrate the use of cold target recoil ion momentum spectroscopy to perform state-selective measurements of the dissociative channels following single-photon double-ionization of H2O. The two dominant dissociation channels observed lead to two-body (OH++H++2e−) and three-body (2H++O+2e−) ionic fragmentation channels. In the two-body case we observe the presence of an autoionization process with a double-differential cross section that is similar to the single-photon double-ionization of helium well above threshold. In the three-body case, momentum and energy correlation maps in conjunction with new classical trajectory calculations in the companion theory paper by Z. L. Streeter et al. [Phys. Rev. A 98, 053429 (2018)] lead to the determination of the eight populated dication states and their associated fragmentation geometry. For the latter case, state-specific relative cross sections, median kinetic energy releases, and median angles between asymptotic proton momenta are presented. This benchmark-level experiment demonstrates that, in principle, state-selective fixed-frame triple-differential cross sections can be measured for some dication states of the water molecule.